2015
DOI: 10.1093/jrr/rrv030
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint-induced stress has little modifying effect on radiation hematopoietic toxicity in mice

Abstract: Both radiation and stresses cause detrimental effects on humans. Besides possible health effects resulting directly from radiation exposure, the nuclear plant accident is a cause of social psychological stresses. A recent study showed that chronic restraint-induced stresses (CRIS) attenuated Trp53 functions and increased carcinogenesis susceptibility of Trp53-heterozygous mice to total-body X-irradiation (TBXI), having a big impact on the academic world and a sensational effect on the public, especially the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Using a laboratory mouse model for chronic restraintinduced psychological stress, the pioneering work on concurrent exposure of Trp53 heterozygous C57BL/6 mice to psychological stress and total body γ-rays showed that psychological stress modulates susceptibility to radiation, causing increased susceptibility to radiocarcinogenesis in Trp53-heterozygous mice underlying the mechanism of Trp53 function attenuation [203]. In recent years, studies using the same chronic restraint system, wild-type C57BL/6J male mice aged 5 weeks and total body exposure to 4 Gy X-rays, showed that psychological stress has minimal modifying effects on radiation-induced hematopoietic toxicity and genotoxicity measured as a peripheral blood histogram, MN in the erythrocytes of bone marrow, and splenocyte CAs (insertions, dicentrics, and fragments), suggesting that chronic restraint-induced psychological stress does not appear to synergize with the clastogenicity of low-LET radiation in wild-type animals [204,205]. Interestingly, in the animal model for psychosocial stress using 6-or 8-week-old male ddY mice (model mouse for spontaneous IgA nephropathy) and SAMP10 mice (model mouse for accelerated senescence), results of concurrent exposure to both psychosocial stress and X-rays at a dose of 3-6 Gy showed increased acute damage, namely, reduced 30-day survival, and decreased erythrocyte and leukocyte counts in the peripheral blood and hypocellular bone marrow, indicating psychological stress promotes radiosensitivity of bone marrow in these particular mice [206].…”
Section: Radiation and Stressmentioning
confidence: 99%
“…Using a laboratory mouse model for chronic restraintinduced psychological stress, the pioneering work on concurrent exposure of Trp53 heterozygous C57BL/6 mice to psychological stress and total body γ-rays showed that psychological stress modulates susceptibility to radiation, causing increased susceptibility to radiocarcinogenesis in Trp53-heterozygous mice underlying the mechanism of Trp53 function attenuation [203]. In recent years, studies using the same chronic restraint system, wild-type C57BL/6J male mice aged 5 weeks and total body exposure to 4 Gy X-rays, showed that psychological stress has minimal modifying effects on radiation-induced hematopoietic toxicity and genotoxicity measured as a peripheral blood histogram, MN in the erythrocytes of bone marrow, and splenocyte CAs (insertions, dicentrics, and fragments), suggesting that chronic restraint-induced psychological stress does not appear to synergize with the clastogenicity of low-LET radiation in wild-type animals [204,205]. Interestingly, in the animal model for psychosocial stress using 6-or 8-week-old male ddY mice (model mouse for spontaneous IgA nephropathy) and SAMP10 mice (model mouse for accelerated senescence), results of concurrent exposure to both psychosocial stress and X-rays at a dose of 3-6 Gy showed increased acute damage, namely, reduced 30-day survival, and decreased erythrocyte and leukocyte counts in the peripheral blood and hypocellular bone marrow, indicating psychological stress promotes radiosensitivity of bone marrow in these particular mice [206].…”
Section: Radiation and Stressmentioning
confidence: 99%
“…Psychological stressors have a major physical component and, similarly, some models of physical stress (such as restraint stress and immobilization stress) can induce PS, at least to some extent (e.g. the chronic restraint model has been used to induce PS [ 24 , 27 ]). As one of the sources of PS, psychosocial stress is also of great concern, and subordinate colony housing has been established as a model in both mice and rats [ 4 , 30 32 ].…”
Section: Concept Of Ps and Its Animal Modelsmentioning
confidence: 99%
“…In laboratory animal models, studies showed that CRIPS could significantly reduce body weight gain from 1 week after the onset of restraint in rats [ 51 ] and from the day following onset in mice [ 27 ], and promote immune suppression, inducing lymphocyte reduction [ 27 , 52 , 53 ]. In rats exposed to continuous stress from photoperiod, temperature and noise, a significantly increased incidence of micronuclei in peripheral red blood cells (RBCs) was observed [ 54 ].…”
Section: Health Consequences Of Ps In Humans and In Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations